ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PT. TUNAS BARU LAMPUNG TBK TAHUN 2018-2020 - Pipit Novila Sari; Riki Alfian (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2023)
The purpose of this study was to determine the financial performance of PT. Tunas Baru Lampung Tbk in 2018-2020. To determine the company's financial performance is to use financial ratio analysis techniques. The ratio analysis used in this study is the liquidity ratio (current ratio, quick ratio, and cash ratio), solvency ratio (DAR ratio, DER ratio, and LTDtER ratio), and profitability ratios (ROA ratio, ROE ratio, and NPM ratio). . The financial statements used in this study are the financial statements of PT. Tunas Baru Lampung Tbk in the 2018-2020 period.Based on the liquidity ratio in the calculation of the current ratio, quick ratio, and cash ratio of PT. Tunas Baru Lampung Tbk in 2018-2020 was classified as poor and produced a fairly low ratio, which resulted in the illiquidity of the company. The solvency ratio performance of PT. Tunas Baru Lampung Tbk in 2018-2020 on the calculation of the DAR ratio, DER ratio, and LTDtER ratio are classified as not good and produce a fairly high ratio, which results in the company having to pay a fairly high burden. Profitability ratio performance of PT. Tunas Baru Lampung Tbk in 2018-2020 on the calculation of the ROA, ROE, and NPM ratios are classified as not good and produce a fairly low ratio, which results in a level of profit that is not maximized.Keywords — Financial Statement Analysis, Financial Performance, Financial Ratios